Rectosigmoidectomy with colorectal anastomosis and nephrectomy due to adenomatous polyps, rectal adenocarcinoma and renal cell carcinoma in a post-COVID-19 patient - Menegassi, Felipe Gustavo Morais; Ciccozzi, Lucas do Valle; Esaki, Pedro Hidekatsu Melo; da Cruz, Maria Elisa Alcântara; Resende, Valéria Cardoso Pinto; de Moura, Flávio José Dutra (Seven Editora, 2023)
Objective: To report a case of a senile patient with colorectal cancer, multiple adenomatous polyps, renal tumor and COVID-19. To analyze the proposed therapies and the relevance of rectosigmoidectomy and nephrectomy as a treatment for rectal adenocarcinoma and renal carcinoma. Case details: Male patient, 82 years old, sought a hospital in 2019 with abdominal pain crises, extensive ecchymosis in the right upper limb, petechia in the lower lip, chills, diaphoresis, hematuria and melena. Colonoscopy showed a vegetating rectal lesion, ascending colon polyps and colonic diverticulosis. In June 2020, developed dyspnea, fever, weakness and general malaise, confirming COVID-19 in laboratory tests, cured two weeks after treatment. In August 2020, the colonoscopy, several sessile polyps and a 5 cm polypoid lesion in the rectum were observed. Biopsy indicated rectal adenocarcinoma. Renal tumor on the right was identified by computed tomography of the abdomen and ultrasound of the total abdomen. The patient was then submitted to rectosigmoidectomy with colorectal anastomosis and nephrectomy on the right. Final considerations: The colonoscopy is still considered an excellent screening test for intestinal polyps. Regarding rectal adenocarcinoma, rectosigmoidectomy is considered an effective curative treatment. Finally, COVID-19 is considered a risk factor for high mortality in cancer patients. DOI:https://doi.org/10.56238/emerrelcovid19-020